1995
DOI: 10.2466/pms.1995.81.3.755
|View full text |Cite
|
Sign up to set email alerts
|

Task-Specific Conjugate Lateral Eye Movements

Abstract: Conjugate lateral eye movements induced by task-specific reflective thought were examined in 10 dextral men. Verbal and spatial stimuli designed to activate reflective thought in the left (verbal) and right (spatial) cerebral hemispheres of the brain were presented tachistoscopically in a darkened environment. Eye movements during reflective thought were monitored and scored using an infrared eye-tracking device. Reflective thought induced by the spatial task produced significantly more leftward conjugate late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…spatial question) is argued to result in a leftward LEM (see also Griffiths & Woodman, 1985). Similarly Galluscio and Paradzinski (1995) found more leftward eye‐movements when adults performed spatial tasks and more rightward and upward movements when verbal tasks were engaged in. Analysis of their participants' performance accuracies revealed the verbal task to be more difficult than the spatial, which may lead to the conclusion that harder tasks were more associated with upward movements.…”
mentioning
confidence: 74%
“…spatial question) is argued to result in a leftward LEM (see also Griffiths & Woodman, 1985). Similarly Galluscio and Paradzinski (1995) found more leftward eye‐movements when adults performed spatial tasks and more rightward and upward movements when verbal tasks were engaged in. Analysis of their participants' performance accuracies revealed the verbal task to be more difficult than the spatial, which may lead to the conclusion that harder tasks were more associated with upward movements.…”
mentioning
confidence: 74%
“…Several aspects of counselors' delivery may have acted to widen the gap between counselor and client in this regard. For instance, when concentrating, people tend to look away; they inhibit eye contact and shift eye gaze as a way to sharpen their attention and enhance information retrieval (Galluscio & Paradzinski, 1995). It is possible, then, that just at the time when clients were looking to the counselors for affective cues, the counselors were looking away.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Falcone and Loder (1984) revealed that upward gaze shifts are positively correlated with the performance on a test that requires divergent thinking and imaginal processing. These upward gaze shifts during integrative thought exercises have been widely documented (for a review, see Previc and Murphy 1997) and appear to persist even in dark rooms (Galluscio and Paradzinski 1995). It is therefore impossible that the upward advantage merely reflects a tendency to avoid stimulation from the lower portion of the visual field.…”
Section: H2mentioning
confidence: 97%